Automatic detection of pulmonary embolism in computed tomography pulmonary angiography using Scaled‐YOLOv4 - Xu, Haijun; Li, Huiyao; Xu, Qifei; Zhang, Zewei; Wang, Ping; Li, Dong; Guo, Li (Medical physics (Lancaster), 2023)
Background Pulmonary embolism (PE) is a common but fatal clinical condition and the gold standard of diagnosis is computed tomography pulmonary angiography (CTPA). Prompt diagnosis and rapid treatment can dramatically reduce mortality in patients. However, the diagnosis of PE is often delayed and missed. Methods In this study, we identified a deep learning model Scaled‐YOLOv4 that enables end‐to‐end automated detection of PE to help solve these problems. A total of 307 CTPA data (Tianjin 142 cases, Linyi 133 cases, and FUMPE 32 cases) were included in this study. The Tianjin dataset was divided 10 times in the ratio of training set: validation set: test set = 7:2:1 for model tuning, and both the Linyi and FUMPE datasets were used as independent external test sets to evaluate the generalization of the model. Results Scaled‐YOLOv4 was able to process one patient in average 3.55 s [95% CI: 3.51–3.59 s]. It also achieved an average precision (AP) of 83.04 [95% CI: 79.36–86.72] for PE detection on the Tianjin test set, and 75.86 [95% CI: 75.48–76.24] and 72.74 [95% CI: 72.10–73.38] on Linyi and FUMPE, respectively. Conclusions This deep learning algorithm helps detect PE in real time, providing radiologists with aided diagnostic evidence without increasing their workload, and can effectively reduce the probability of delayed patient diagnosis.